An investigation of the prevalence of financial stress and its effect on employee performance at the workplace. Case of Turnall Holdings Limited. - Magodhini, Prisca (Midlands State University, 2017)
This research was a case study of Turnall Holdings Limited which sought to establish the prevalence of financial stress and examine its effect on workplace performance of employees. The study was motivated by the fact that some employees are extrinsically motivated whilst others are not, yet the employer was trying to combat the current corporate financial constraints through eliminating all employee financial benefits. As such, Turnall employees were found to be facing financial difficulties as denoted by low salaries and wages as well as late payment of these, following a salary cut of 7-15% in May 2016 and a further cut of 50% in September 2016. Also, employees’ financial benefits were eliminated, they spent up to four months without being paid and working days (for some employees) were also reduced resulting in employees getting half salaries. Additionally, as a result of financial problems, employees were found to be associated with high and rising debt and credit levels, low saving rates, frequent requests of salary advances, high absenteeism rates and they sometimes took long breaks. The objectives of this study were to investigate prevalence of financial stress, identification of its predictors and its consequences, to establish the strategies being adopted to cope with it and to investigate its effect on employee performance at the workplace. Various literature sources in relation to the study tittle were reviewed and critically analyzed, which inturn informed thisstudy work. The study adopted a combination of the descriptive and explanatory research designs. Population in this case was also the study’s target population, which comprised of all Turnall employees totaling 110 inclusive of employees and managers. A sample of 59 respondents was employed and it was based on the stratified random sampling technique. Out of the 59 questionnaires that were dished out, 42 were retrieved by the researcher and the obtained raw data was presented in tabular format and was analyzed using the STATA 11 statistical package, utilizing the regression tool and frequency computations. The study thus established that undeniably, financial stress is prevalent among Turnall employees and it is predicted by demographic factors as well as other independent factors. Its consequences include high absenteeism rates, lateness at work and health problems and employees are currently adopting some strategies to cope with it, which include menial jobs, collective saving programs and financial management strategies. It was also established that these consequences are affecting employee performance through reduction in productivity per worker. The main study recommendations are that the employees should have stress management skills through financial education, advice and counselling and the employer on the other hand should explore any other alternative turnaround strategies to revive the company from financial distress other than continuously cutting down on wages and salaries and retrenching its workforce. Further studies are thus recommended where productivity trends are established and related to financial stress over a specific period of time since productivity in this case was measured through inference.